2019
DOI: 10.1002/adfm.201806485
|View full text |Cite
|
Sign up to set email alerts
|

Multicore Liquid Perfluorocarbon‐Loaded Multimodal Nanoparticles for Stable Ultrasound and 19F MRI Applied to In Vivo Cell Tracking

Abstract: Ultrasound is the most commonly used clinical imaging modality. However, in applications requiring cell-labeling, the large size and short active lifetime of ultrasound contrast agents limit their longitudinal use. Here, 100 nm radius, clinically applicable, polymeric nanoparticles containing a liquid perfluorocarbon, which enhance ultrasound contrast during repeated ultrasound imaging over the course of at least 48 h, are described. The perfluorocarbon enables monitoring the nanoparticles with quantitative 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 66 publications
4
114
0
Order By: Relevance
“…In contrast, a typical deviation of the PFCE content between different batches prepared with conventional sonication is larger, typically around 10%. 9 Scanning electron microscopy (SEM) further confirmed that the NPs were spherical in shape and displayed some polydispersity, which is generally typical for PLGA particles. The majority of NPs had a radius between 100 and 200 nm, similar to DLS results.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…In contrast, a typical deviation of the PFCE content between different batches prepared with conventional sonication is larger, typically around 10%. 9 Scanning electron microscopy (SEM) further confirmed that the NPs were spherical in shape and displayed some polydispersity, which is generally typical for PLGA particles. The majority of NPs had a radius between 100 and 200 nm, similar to DLS results.…”
Section: Resultsmentioning
confidence: 78%
“… 21 , 25 , 43 As a starting point for our study, we used the composition of our conventional batch formulation of PFCE–PLGA-NPs that were approved for a clinical trial. 9 , 24 At the beginning, we kept all main parameters, such as the concentration of the surfactant [poly(vinyl alcohol) (PVA)] and PLGA, the same as in the batch method, with dichloromethane (DCM) as a solvent for the organic phase, focusing on the effect of flow parameters. 22 24 The ratios between the three phases, which correspond to the volumes used in the conventional method, can be adjusted directly in the microfluidic system by changing the flow rates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations